2017
DOI: 10.1007/s40544-017-0170-x
|View full text |Cite
|
Sign up to set email alerts
|

Tribological evaluation of environmentally friendly ionic liquids derived from renewable biomaterials

Abstract: Unlike most of the conventional ionic liquids (ILs) derived from non-renewable resources, five environmentally friendly ILs ([Ch][AA] ILs) derived from amino acids (AAs) and choline (Ch) were synthesized using biomaterials by a simple, green route: acid-base reaction of Ch and AAs. The thermal and corrosion properties, as well as viscosity, of the prepared ILs were examined. The results revealed that the anion structure of ILs plays a dominant role in their thermal and viscosity behavior. These ILs exhibited l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Gong et al [90] and Lhermerout et al [91] discussed the new progress in ionic liquids. Jiang et al [92] reported environmentally friendly ILs ([Ch][AA] ILs) derived from amino acids (AAs) and choline (Ch) synthesized by using biomaterials through a simple, green route. Their results indicated that these ILs exhibit good frictionreducing and anti-wear properties as lubricants for steel/steel contact, which is related to the formation of a physically adsorbed film on the metal surface during friction.…”
Section: Molecular Lubrication 2311 Ionic Liquid Lubricationmentioning
confidence: 99%
“…Gong et al [90] and Lhermerout et al [91] discussed the new progress in ionic liquids. Jiang et al [92] reported environmentally friendly ILs ([Ch][AA] ILs) derived from amino acids (AAs) and choline (Ch) synthesized by using biomaterials through a simple, green route. Their results indicated that these ILs exhibit good frictionreducing and anti-wear properties as lubricants for steel/steel contact, which is related to the formation of a physically adsorbed film on the metal surface during friction.…”
Section: Molecular Lubrication 2311 Ionic Liquid Lubricationmentioning
confidence: 99%
“…An increase in the cost of petroleum-based lubricants and environmental law regulations has caused vegetable oils to become increasingly attractive in a wide range of metal-forming applications [ 15 , 16 , 17 ]. Sunflower, coconut, soya bean, peanut, linseed, and rapeseed oils are considered as potential bio lubricants [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, liquid lubricants are mainly divided into two categories-natural and synthetic lubricants. Natural lubricants include some animal fat, vegetable oils, and mineral oils [2]. Synthetic lubricants commonly contain synthetic hydrocarbon, synthetic ester, and perfluoropolyethers (PFPEs), and are widely used in special conditions, such as applications that require high temperature stability, low saturated vapor pressures, excellent extreme pressure, and oxidation stability [3].…”
Section: Introductionmentioning
confidence: 99%